School to work transition: Employment and expectations of former madrasa students in Cox’s Bazar, Bangladesh - Ahmed, Md. Shakil; Arman, Mohammad Raied; Hossain, Marjan; Rahman, Khandker Wahedur; Rahman, Nuzaba Tahreen (Elsevier, 2024)
This article was published in the International Journal of Educational Development [©2024 Rights managed by Elsevier] and the definite version is available at: https://doi.org/10.1016/j.ijedudev.2024.103020 The Article's website is at: https://www.sciencedirect.com/science/article/pii/S0738059324000427?via%3Dihub